Hubungan Pijat Bayi dengan Perbaikan Status Gizi pada Baduta Terkait 1.000 HPK di Wilayah Kerja Puskesmas Pati II - Siti Muawanah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
Baby massage is one of the hereditary treatments for babies that are always healthy, in addition to these habits can also help overcome the problem of nutritional status. One of the causes of malnutrition is nutrition that is not fulfilled while in the womb, but this can be pursued before the child is 2 years old so that the child can be tall and large, one of them with baby massage intervention. Infant massage stimulation can help improve the status of a child's nutrition and stimulate the child's growth and development. The purpose of this study was to determine the relationship between infant massage and nutritional status of the two million children shown in the 1,000 HPK group in the context of accelerating nutritional improvement. This type of research used analytic observation with cross sectional method. The samples used were 45 babies under the age of two years. The sampling technique uses total sampling. The results showed that babies who did massage babies were 24 (53.3%), and had good nutritional quality as many as 19 (42.2%). There is a relationship between baby massage with the nutritional quality of infants under two years of age, with a p value of 0.001. This research is expected that parents pay more attention to the nutritional quality of their babies through routine baby massage, which is every 1-2 months. because massaging movements from head to toe make the body more easily in delivering nutrients to blood vessels, blood circulation, improve cognitive function of children, to make the baby avoid nutritional problems.